MOTIVATION AND CONSEQUENCE OF INDIVIDUALâS INVOLVEMENT IN SOCIAL NETWORK SITES: A STUDY OF SOCIAL COMPUTING OF INTER COLLECTIVISTINDIVIDUALIST CULTURAL VALUE - Abdillah, Willy; HM, Jogiyanto; Handoko, Hani (Journal of Indonesian Economy and Business, 2012)
This research aims to examine the empirical model of social computing. Research model is developed upon the social influence factors, technology acceptance model, psycho-social wellbeing, and culture value. Research design employed online survey questionnaire. Data of 433 samples were analyzed using Partial Least Square (PLS) technique. Results suggest that proposed model has met criteria of goodness-of-fit model and indicated that Identification and Compliant are the motivation factors of desire to involve in social network sites (SNS) and involvement in SNS predicts depression and loneliness. This research also finds that motivation of individual to involve in SNS and its impact are different among collectivist and individualist. Implications for stakeholders and further research are discussed.Keywords: social computing, social influence factors, psychosocial wellbeing, social network sites, individual culture values, and PLS.